A novel hiPSC-derived system for hematoendothelial and myeloid blood toxicity screens identifies compounds promoting and inhibiting endothelial-to-hematopoietic transition. (December 2019) - Elcheva, Irina; Sneed, Mechelle; Frazee, Scott; Liu, Zhenqiu; Zhu, Junjia; Wood, Tyler; Hendrickson, Sara; Oehler, Chuck; Garcia, Brad; Spiegelman, Vladimir S.
Abstract: The exposure to toxic environmental and pharmaceutical substances can pose a long-term risk to human's health. In this study, we sought to investigate the potential of our recently developed method for induction of myeloid hematoendothelial and blood cells by overexpression of two transcription factors, GATA2 and ETV2, in human induced pluripotent stem cells (hiPSCs) for toxicity screening. For the primary screen in a high-throughput format, we selected twenty-two chemicals with various degrees of cytotoxicity available from the NIEHS National Toxicology Program (Tox21). The compounds were applied during the endothelial-to-hematopoietic transition and to differentiated myeloid progenitors growing in suspension. The system was capable of identifying compounds with both inhibitory and favorable effects on hematopoietic network, changes in expression of hematopoietic markers, and mitochondrial and cytotoxicity. The findings were confirmed and further investigated by secondary screens, colony forming cell assay, and gene expression profiling. The hematoendothelial toxicity of 5-fluorouracil, berberine chloride, and benzo(a)pyrene is characterized by the inhibition of cell division and a shift of hematopoietic programming to non-hemogenic endothelial and mesenchymal fates. This study demonstrates the feasibility of transcription factor (TF)-based differentiation systems to monitor endothelial and hematotoxicity and serves as an informative platform for screening myelosuppressive or stimulatory drugs and mechanistic studies of their action. Highlights: The protocol for direct induction of hematoendothelial program was adapted to 96-well format suitable for toxicity screening. The system identifies compounds inhibiting and promoting endothelial-to-hematopoietic transition (EHT). EHT inhibition is associated with cell cycle arrest and a switch to non-hemogenic endothelial and mesenchymal fates.